Saturday

April 19, 2014

April 19, 2014

Posted by **jas20** on Friday, March 2, 2007 at 2:19am.

6a^2-5a+1

so far what i have is this:

(3a-1)(3a )

If you expand your answer you will not get the original expression, so you are wrong.

hint: 3a x ?a = 6a^2

**Related Questions**

Math- factoring - Show all work and factor completely. 6a^2+5a-4 (6a^2+8a)-(3a-4...

math help - I need help factoring this out 6a^2-5a+1 okay so now after revising...

algebra - Given g(x) = –2x – 1, find g(3a). G(3a)=-2(3a)-1 = -6a-1 = -5 is this ...

Math - 6a(3a-2) + 12b(3a-2) Is it correct if i multiplied 6a by 3a then 6a by -2...

algebra - 3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals ...

alg - multiply: 15a^2 / 14 * 7 / 5a a) 3a^2 / 2 b) 6a c) 21a / 2 d) 3a / 2

Math - Factorize the following expressions: 1) 6a(3a-2)+12b(3a-2) I got : (3a-2...

Math~Polynomials - 1)6g+8k-9g+2k(1point) 3g+10k -3g+10k*** 17gk 10k-3 2)-4x+6x^2...

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...